Socio-Pedagogical Competences of Specialists in Social Work with Children and Youth with Disabilities and with Their Families - Остролуцька, Л. (Київський національний університет імені Тараса Шевченка, 2017)
The article raised the question of specialization in: social work with persons who have disabilities. Criteria of social and pedagogical competences, competent approach and actual needs of practicing specialists, their preparation for work with persons who have disabilities are considered.

У статті піднято питання щодо спеціалізації в соціальній роботі, а саме: соціальної роботи з особами з інвалідні- стю. Розглянуто критерії соціально-педагогічних компетенцій і компетентнісного підходу та актуальних потреб практикуючих спеціалістів, їх підготовки до роботи з особами з інвалідністю.
Соціально-педагогічні компетенції спеціалістів соціальної роботи з дітьми та молоддю з інвалідністю та їх сім’ями
Keywords: соціально-педагогічні компетенції спеціалістів соціальної роботи; компетентність; соціальна ро- бота; професійний портрет спеціаліста соціальної роботи з особами з інвалідністю.; social-pedagogical competences of specialists of social work; competence; social work; professional portrait of specialist of social work with persons with disabilities.